Bimbingan Terhadap Majlis Taklim Tentang Moderasi Beragama Di Desa Palesanggar Kec. Pegantenan Pamekasan - AR, Samsul; Hasbullah, M.; Faiz, Jamil (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2024)
Religious moderation is crucial to instill in the congregation of the Baitul Muttaqin Majlis Taklim as a key pillar of defense against radical ideologies within the family.** The family is a vital element in safeguarding the unity of the Republic of Indonesia from the threats of violence. This guidance on religious moderation aims to equip the members of the Majlis Taklim with a moderate understanding that they can later teach within their own families. Parents, as role models in the family, play a significant role in providing moderate values to their children and household. This guidance is a form of community service intended to offer understanding, explanation, and direction on the importance of cultivating moderate principles within the family. The guidance employs a participatory action research approach, where the author is directly involved in mentoring through the Majlis Taklim in Palesanggar Village, Pegantenan District, Pamekasan.